Individual variability of Scots pine Pinus sylvestris L. by the drought resistance features in forest-steppe pine forests of south Siberia - N. A. Tikhonova; I. V. Tikhonova (Сибирский лесной журнал, 2016)
The drought resistance of trees in the Scots pine Pinus sylvestris L. populations was studied under forest steppe conditions of southern Siberia. We found large differences amongthe treesin the time and rate of needles dehydration. In the populations of the more arid growing conditions (Shira, Balgazyn) the rate of loss 50 % of the water was three to four times lower than in the population of the more favorable conditions for growth (Minusinsk). It has been established that the variability of water-holding capacity of needles from individual trees in populations varies from high to very high levels. On the contrary, for the water absorption capacity of needles characteristically has variability, as within population and between them. Is marked a great assessment reliability of water holding capacity of the needles under the pooled analysis of absolute and relative indicators of dynamics of the needles degradration. We investigated the correlation of needles’ water retention signs with a height and heterozygosity of trees. It was found that under more favorable conditions of the growth the large part of sample are the trees with a direct connection between heterozygosity and drought resistance of tree and in the worst conditions – with a reverse. The correlations of water-holding capacity of needles with the height of the tree are ambiguous: in the Minusinsk sample, the most of drought-resistant trees are characterized by better growth, in Balgazyn population – conversely. Some dwarf individuals from the Balgazyn and Shira populations in terms of drought tolerance are at same level as the typical trees, among the less drought-resistant trees found as dwarfs, and typical trees. It was concluded that there are trees in populations with different strategies to adaptation to the moisture deficit.